Hybrid and Multi-Level Adaptive Governance for Sustainable Urban Transformations in the Global South: A Secondary City Case Study - Yasmin, Tahmina; Farrelly, Megan A.; Rogers, Briony C.; Krause, Stefan; Lynch, Iseult (Frontiers in Water, 2022)
The water governance crisis has critical implications for the transformation of cities through the establishment of sustainable water management practices. Adaptive governance approaches, with their potential to address global water governance challenges, are emerging in the context of the global South (GS). A key feature of adaptive governance is its enabling context or hybridized governance approach which bridges organizational and network activities across multiple implementation scales. Transforming urban water management towards sustainable water governance practices requires flexibility and agility, and a willingness to enable new ideas, features often associated with smaller and newer cities (secondary cities) which are less constrained than the major cities. However, unpacking their potentiality and the scope of such secondary cities to lead the way in transitioning to sustainable water governance remains under-researched. To address this gap, a qualitative study in a representative GS secondary city (Mymensingh in Bangladesh) was undertaken to investigate whether national and local strategies directed towards improving the governance and management capacity of the local municipality are yielding sustainable transformations. We identified a significant shift within the governance regime that influences existing power dynamics and decision-making for the delivery of urban water services. Within the traditional state-led governance structure, a hybridized governance is emerging that builds both institutional and actor capacity. However, these hybridized governance activities are strongly dependent on (international) donor investment and guidance, therefore the presence or absence of donor support will likely determine the impact of these activities in the future.